Images of Law in Chinese Crime Fiction - Morais, Isabel (2014)
Crime fiction in China emerged in the 1890s in translations of Western works, and evolved from the mere imitation of Western crime fiction to becoming an autonomous literary genre. Despite fluctuations in popularity, the genre of Chinese crime fiction, the plots of which are based on true cases, has retained a reasonably constant presence on the literary scene, and has captured the popular imagination in contemporary China and, more recently, across the world. After the demise of Mao, under whose governance the genre was banned, the government of the early Deng regime began to favor so-called “legal system literature” (fazhi wenxue), and aimed to use it to propagate moral principles and maintain political control in opposition to writers who strived for independence and originality. Since the mid and late 1980s, which were considered the heyday of Chinese crime fiction, and the expansion of the legal system and legal institutions, crime fiction has served to illuminate the role of law and to display new social perceptions. To investigate these attitudes, I focus on works of contemporary Chinese crime fiction by arguing that they are expressions of a confluence of cultural exchange and new trends. Several factors may have contributed to such a change, from the impact of the cinema and television serials in China to the celebrity status of Chinese detectives, lawyers and judges both as crime solvers and writers in the Chinese mainland and amongst the Chinese writing diaspora. An important finding is that besides giving detailed descriptions of legal procedures, all of the works studied have clearly shifted away from the traditional formula of Chinese crime fiction, that is, of the quest of a hero for justice, punishment, and revenge, to focus on the process of solving crime and the rendering of justice through legal processes. It seems that crime fiction is becoming crucial in conveying a new understanding of citizen’s rights in an attempt to fit into ongoing contemporary debates on universalistic notions of justice and the competence of legal institutions to provide justice to increasingly marginalized sectors of contemporary China.